Pelaksanaan Pemilihan Kepala Desa e-Voting di Kabupaten Magetan - Andria, Andria (Universitas Nusantara PGRI Kediri, 2023)
The development of information technology has also created various innovations, including in the government sector, such as the implementation of village head elections using the e-voting system. In this activity, the author acts as a village head election committee with the main task of preparing the Temporary Voter List (DPS) and preparing the Permanent Voter List (DPT). For the author, this activity is a form of community service activity. The stages of implementing village head elections include: formation of a committee, coordination meetings, registration and determination of village head candidates, voting via an e-voting system, announcement of results, and ending with the disbandment of the committee. The method of implementing service uses qualitative methods. The implementation of village head elections using the e-voting system in Magetan Regency ran in an orderly and safe manner.